LIRIK LAGU ‘LUAHANKU’ DI MEDIA SOSIAL (ANALISIS ISI PESAN DAKWAH) - Saleha, Sitti (An-Nida : Jurnal Komunikasi Islam, 2025)
This study aims to analyze the da'wah messages contained in the lyrics of the song "Luahanku" composed by Ustadz Adnin Roslan, as well as to explore the role of social media in strengthening the dissemination of these messages. This study analyzes the da’wah messages in the song "Luahanku" by Ustadz Adnin Roslan, focusing on the values of aqidah (faith), akhlak (morality), and syari’ah (Islamic law) conveyed through the lyrics, using qualitative content analysis with a cognitive semantic approach. The research also explores how social media platforms like Facebook, Instagram, and YouTube amplify these messages, enabling wider dissemination and interaction between the message sender and audience. Findings show that the song emphasizes strengthening belief in Allah (aqidah), promoting ethical behavior and self-improvement (akhlak), and providing guidance for religious duties (syari’ah), with social media playing a key role in spreading and engaging audiences through likes, comments, and shares. This study highlights the effective combination of meaningful lyrical content and digital media as a powerful tool for contemporary Islamic da’wah.